Snow sports trauma and safety : conference proceedings of the International Society for Skiing Safety: 21st volume - Scher, Irving S.; Greenwald, Richard M.; Petrone, Nicola (Springer, 2017)
This book is open access under a CC BY-NC 2.5 license. This book covers the latest in snow sport epidemiology, snow sport injuries and treatment, and biomechanical/mechanical engineering related to snow sports injuries (mechanisms of injury, injury prevention by equipment design, injury prevention by design of resort features, and more). It brings together a collection of papers from the International Congress on Ski Trauma and Safety (the biennal meeting of the International Society for Skiing Safety) and presents the latest research on the effectiveness of winter sports equipment, the behavior of winter sports participants, and the epidemiology and biomechanics of winter sports injuries. This is an ideal book for researchers and professionals working in the field of sports medicine and safety. This book also: Covers the latest body of literature dealing with safety in winter sports as well as the prevention and treatment of injuries sustained by participants in these activities Broadens readers' understanding of snow sport injury prevention research Illustrates ways safety standards for snow sports can be improved based on evidence-based research.
International conference proceedings.
Keywords: Skis and skiing -- Wounds and injuries -- Congresses.; Skis and skiing -- Health aspects -- Congresses.; elektronické knihy; electronic books